The knowledge on oxygen delivery devices and awareness of oxygen prescription among nurses / N Syarmimi Izzati Mohd Zakuan, Nur Shazwani Shahir and Siti Norfitriyah Zakaria - Mohd Zakuan, N Syarmimi Izzati; Shahir, Nur Shazwani; Zakaria, Siti Norfitriyah (Faculty of Health Sciences, 2015)
Background: Oxygen is a drug that is commonly used in secondary care. As for any other drugs, it is important to choose appropriate dose and delivery systems for oxygen in order to meet patient’s needs and hence to achieve therapeutic goals. All health care professionals must know how to handle oxygen, as well as oxygen administration because it is vital to achieve therapeutic benefits for the patient. Objective: The purpose of this study is to determine the knowledge and practice of decision for prescription and administration of oxygen therapy among nurses in medical ward of Hospital Ampang. Method: A cross-sectional study design was carried out at medical wards in Hospital Ampang. A self-administered questionnaire was distributed to 48 nurses in medical ward over a period of one month. Result: The result of this study showed most of the staff nurse in the medical ward had good knowledge regarding oxygen delivery devices but had poor awareness on oxygen prescriptions. It was reported that only 29 participants with percentage of 60.4% had good knowledge on oxygen delivery devices, while 13 participants with the precentage of 27.1% showed moderate level and 12.5% of participants had poor knowledge on oxygen delivery devices. Besides that, most of the participants was reported to have poor awareness on oxygen prescriptions with the percentage of 70.8% (n=34), while about 22.9% of participants showed moderate level of awareness, and only 6.3% reported to have good awareness on oxygen prescriptions. The result show there is no association between knowledge of oxygen delivery devices and awareness of oxygen prescription among nurses with the p value of 0.051. Conclusion: The overall score for nurses in medical wards show good knowledge regarding oxygen delivery devices do not guarantee the nuses have good prescription practice. There is clearly a need to place a greater emphasis on oxygen therapy in medical nurses and nursing education and to implement ongoing revision during resident training into the ward. Also, there is the requirement for the development of educational programs and protocols for health care personnel on oxygen therapy must become mandatory towards decreasing errors in oxygen administration.